Towards Sustainable Low-Embodied-Carbon Concrete Alternatives - AIDEH, MAJD RASMI AHMAD (2024)
This paper evaluates the benefits of using environmentally sustainable low-embodied carbon alternatives to traditional concrete, as the concrete industry is responsible for significant global greenhouse gas emissions due to its environmental impact. This research conducts a comprehensive analysis to identify the environmental effects of alternative materials compared to Ordinary Portland Concrete. It specifically focuses on the amount of carbon dioxide (CO2) and carbon dioxide equivalent (CO2-Eqv) emissions associated with different concrete compressive strength grade classifications. The analysis includes a comparison of normalized carbon emissions data across a wide range of papers and reporting formats using the unit of kilograms of carbon per megapascal (MPa). The paper discusses the impact of the compressive strength grade, the type of alternative material, and the quantity of replacement. The findings indicate that replacing Ordinary Portland Concrete with alternatives such as Ground Granulated Blast Furnace Slag (GGBS), Fly Ash (FA), and Alkali-Activated materials (AA) results in enhanced efficiency by reducing the carbon footprint. Using the type of (GGBS) gives a superior reduction at most of the selected compressive strength grades. The carbon emissions vary based on the replacement of Ordinary Portland Cement (OPC) with alternative materials during the production of concrete. Therefore, it is crucial to thoroughly assess the selection of combinations for each specific concrete grade to achieve positive environmental results in comparison to (OPC).